2016 Evaluation of Foliar Fungicides for Disease Control in Peanut, Jay, FL - Michael J. Mulvaney; Robert (Bob) Kemerait; John D. Atkins; Nicholas S. Dufault (EDIS, 2017)
This report includes a summary of the 2016 foliar fungicide programs for control of early and late leaf spot and white mold (southern stem rot) in peanut at Jay, Florida. It shows the effectiveness of 13 fungicide programs for disease control. All programs contained active ingredients for the control of white mold (Sclerotium rolfsii) except the Bravo treatment (program #2), which was considered a control. These data represent only one year at one location, and readers are cautioned that test results should be considered over several locations and years before final conclusions are considered valid. These data are meant to serve as a guide in the selection of effective fungicide programs for peanut.